Acceleration of CO2 insertion into metal hydrides: ligand, Lewis acid, and solvent effects on reaction kinetics. Issue 32 (16th July 2018) - Heimann, Jessica E.; Bernskoetter, Wesley H.; Hazari, Nilay; Mayer, James M.
Abstract : Kinetic studies of CO2 insertion into transition metal hydrides provide evidence about the nature of the rate-determining transition state. Abstract : The insertion of CO2 into metal hydrides and the microscopic reverse decarboxylation of metal formates are important elementary steps in catalytic cycles for both CO2 hydrogenation to formic acid and methanol as well as formic acid and methanol dehydrogenation. Here, we use rapid mixing stopped-flow techniques to study the kinetics and mechanism of CO2 insertion into transition metal hydrides. The investigation finds that the most effective method to accelerate the rate of CO2 insertion into a metal hydride can be dependent on the nature of the rate-determining transition state (TS). We demonstrate that for an innersphere CO2 insertion reaction, which is proposed to have a direct interaction between CO2 and the metal in the rate-determining TS, the rate of insertion increases as the ancillary ligand becomes more electron rich or less sterically bulky. There is, however, no rate enhancement from Lewis acids (LA). In comparison, we establish that for an outersphere CO2 insertion, proposed to proceed with no interaction between CO2 and the metal in the rate-determining TS, there is a dramatic LA effect. Furthermore, for both inner- and outersphere reactions, we show that there is a small solvent effect on the rate of CO2 insertion. Solvents that have higher acceptor numbers generally lead to faster CO2 insertion. Our results provide an experimental method to determine the pathway for CO2 insertion and offer guidance for rate enhancement in CO2 reduction catalysis.